REA value chain and supply chain - Huňka, František; Žáček, Jaroslav; Meliš, Zdeněk; Ševčík, Jaroslav (Univerzita Pardubice, 2011)
Value chain model is a network of business processes that are bound by inflows and outflows resources. Resource Event Agent (REA) is an enterprise domain ontology based on value modeling perspective of business processes. REA value chain is a sequence of REA models (processes) utilizing the REA ontology that are interweaved into the chain by resource flows among them. Contrary to, supply chain is the entire network of enterprises involved in providing a particular product or service to an end customer. The paper focuses on finding common properties between supply chain and value chain, especially REA value chain and possibilities of REA ontology to be used to model supply chain. After describing the basic fundaments of the REA ontology, REA value chain and supply chain, the paper deals with the examining the principal aspects of the REA value chain that would bring closer and stronger bonds between the REA value chain and supply chain. In this way, the REA ontology can be potentially utilized as an integration of a value chain and a supply chain concept. Achieved findings and results are discussed and illustrated in accompanied figures.
Keywords: value modeling business ontology; REA ontology; value chain; supply chain